The effect of transfer pricing, thin capitalization, and foreign ownership on tax avoidance using tax haven utilization as moderation - Jazmi, Variant Zulfadhli; Masripah, Masripah (Educoretax, 2025)
This quantitative study analyzes the impact of Transfer Pricing, Thin Capitalization, and Foreign Ownership on Tax Avoidance, with Tax Haven Utilization as a moderating variable. Data is sourced from annual reports and financial statements of multinational companies listed on the Indonesia Stock Exchange from 2021–2023. Using purposive sampling, the study includes 63 companies, totaling 189 observations. Panel data regression analysis was conducted with STATA 17 at significance levels of 5%, 10%, and 25%. Results show that Transfer Pricing, Thin Capitalization, and Foreign Ownership do not significantly affect Tax Avoidance. However, Tax Haven Utilization significantly strengthens the relationship between Thin Capitalization and Tax Avoidance but does not moderate the effects of Transfer Pricing or Foreign Ownership. This suggests that tax haven jurisdictions primarily influence the impact of capital structure on tax avoidance rather than ownership or pricing policies. This study enhances understanding of Tax Avoidance determinants in multinational firms in Indonesia. Findings provide valuable insights for academics and practitioners in improving tax oversight strategies. Future research should explore additional factors such as corporate tax compliance and international tax regulations.